Overt and covert customer data collection in online personalized advertising: The role of user emotions - Lamprinakos, Grigorios; Magrizos, Solon; Kostopoulos, Ioannis; Drossos, Dimitrios; Santos, David (Journal of business research, 2022)
Due to its immense popularity amongst marketing practitioners, online personalized advertising is increasingly becoming the subject of academic research. Although advertisers need to collect a large amount of customer information to develop customized online adverts, the effect of how this information is collected on advert effectiveness has been surprisingly understudied. Equally overlooked is the interplay between consumer’s emotions and the process of consumer data collection. Two studies were conducted with the aim of closing these important gaps in the literature. Our findings revealed that overt user data collection techniques produced more favourable cognitive, attitudinal and behavioral responses than covert techniques. Moreover, consistent with the self-validation hypothesis, our data revealed that the effects of these data collection techniques can be enhanced (e.g., via happiness and pride), attenuated (e.g., via sadness), or even eliminated (e.g., via guilt), depending on the emotion experienced by the consumer while viewing an advert.